Digital Transformation for Educational Development in Sub-Saharan Africa - Gbadebo, Adedeji Daniel (International Journal of Social Science and Religion (IJSSR), 2024)
Digital transformation holds significant promise for revolutionizing education in Sub-Saharan Africa (SSA). This paper examines the challenges of digital transformation in education in the SSA region. We observed that the challenges are multifaced, including infrastructure deficits, access and equity barriers, digital literacy gaps, financial constraints, policy challenges, and regulatory barriers. To overcome these challenges, the paper offers some recommendations that can help the SSA countries to unlock the transformative power of digital technologies to advance education, empower learners, and build a brighter future. Amongst other, the paper suggests that stakeholders must adopt an integrated approach to infrastructure development, promote equitable access and inclusion, invest in capacity building and skills development, localize educational content, mobilize financial resources, enact policy and regulatory reforms, and foster collaborative partnerships.